Effects of Intranasal Administration of Oxytocin and Vasopressin on Social Cognition and Potential Routes and Mechanisms of Action - Shuxia Yao; Keith Maurice Kendrick (MDPI AG, 2022)
Acute and chronic administration of intranasal oxytocin and vasopressin have been extensively utilized in both animal models and human preclinical and clinical studies over the last few decades to modulate various aspects of social cognition and their underlying neural mechanisms, although effects are not always consistent. The use of an intranasal route of administration is largely driven by evidence that it permits neuropeptides to penetrate directly into the brain by circumventing the blood-brain barrier, which has been considered relatively impermeable to them. However, this interpretation has been the subject of considerable debate. In this review, we will focus on research in both animal models and humans, which investigates the different potential routes via which these intranasally administered neuropeptides may be producing their various effects on social cognition. We will also consider the contribution of different methods of intranasal application and additionally the importance of dose magnitude and frequency for influencing G protein-coupled receptor signaling and subsequent functional outcomes. Overall, we conclude that while some functional effects of intranasal oxytocin and vasopressin in the domain of social cognition may result from direct penetration into the brain following intranasal administration, others may be contributed by the neuropeptides either entering the peripheral circulation and crossing the blood-brain barrier and/or producing vagal stimulation via peripheral receptors. Furthermore, to complicate matters, functional effects via these routes may differ, and both dose magnitude and frequency can produce very different functional outcomes and therefore need to be optimized to produce desired effects.